Fintech and bank stability in a small-open economy context: The case of Kenya - Jared Osoro; Kiplangat Josea Cheruiyot (Kenya Bankers Association (KBA), 2023)
This paper seeks to examine the effect of Fintech credit on bank stability using an unbalanced panel dataset of 37 commercial banks in Kenya between 2013 and 2020. The recent evolution of Fintech comes with the promise of being both revolutionary and disruptive. The temptation of a unidirectional expectation that effects of Fintech will only be positive masks the potential destabilization effects, hence the motivation to examine possibility of its being a source of fragility in the banking sector in Kenya. We employ both static panel models and a dynamic panel of System Generalized Method of Moments (GMM) that lead us to the conclusion that Fintech credit has not occasioned concerns of market fragility. If anything, the empirical results reveal that the FinTech credit is associated with higher bank stability in the sense that FinTech intermediated credit is associated with a higher Z-score suggesting higher overall bank stability. The relationship is however nonlinear, with the squared term of the FinTech credit being negative and statistically significant. We infer that the influence of FinTech on bank stability is inverted "U" type relationship. Bank-specific factors such as equity to assets, asset quality and cost-to-income rations having a strong influence on bank stability. That is a pointer to the possibility of the current magnitude of Fintech credit - the possible conduit of instability - not being associated with fragility, with the likelihood of that changing as the its share of bank assets grows with time.
Keywords: 330; Bank Stability; FinTech; Kenya